Comparison of a ‘Ship-type’ Brazier found in Knidos underwater research and ‘Ship-type’ Braziers of the Roman Imperial Period - Doksanalti, Ertekin M.; Aslan, Erdogan (Rei Cretariae Romanae Fautorum Acta, 2022)
Braziers, specially fabricated to warm up the ship and carry out cooking activities, were introduced. Different ship braziers were produced, varying depending upon the places and conditions in which they were used. This study examines different types of braziers (referred to here as ship-type braziers), which have been found underwater. Using data taken from a shiptype brazier found during the Knidos underwater researches and a brazier on exhibit at the Antalya Archaeological Museum, this article aims to determine the chronological and typological development of the braziers found in different spots along the sea courses of ancient ships in the Mediterranean Basin. Ship-type braziers, whose names have been designated according to their findspots, were used from the late 1st century BC until the 10th century AD. Considering their characteristics, the ship-type Knidos braziers have been determined to date back to the1st century BC and were used up to the 1st century AD.